2015
DOI: 10.2169/internalmedicine.54.3973
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Treatment of a Pregnant Woman with Progressive Gastric Cancer

Abstract: We herein describe a rare case of gastric cancer that was treated with chemotherapy during pregnancy. A woman in her thirty's at 23 weeks of gestation was admitted to the hospital with epigastralgia and left cervical lymph node swelling. She had been previously diagnosed with metastatic adenocarcinoma at another hospital. Findings from a CT scan and esophagogastroduodenoscopy revealed progressive gastric cancer, and the pathology indicated poorly differentiated adenocarcinoma. Chemotherapy was administered at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…However, Nishie et al applied chemotherapy to a pregnant woman with metastatic gastric adenocarcinoma who was 23 weeks pregnant and delivered her at 32 weeks with a caesarean section. The child continued to show no abnormalities at 12 months after delivery (11). Ueno et al reported that the treatment of gastric cancer during pregnancy depends on the stage of the disease, the week of pregnancy and the development of fetus at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…However, Nishie et al applied chemotherapy to a pregnant woman with metastatic gastric adenocarcinoma who was 23 weeks pregnant and delivered her at 32 weeks with a caesarean section. The child continued to show no abnormalities at 12 months after delivery (11). Ueno et al reported that the treatment of gastric cancer during pregnancy depends on the stage of the disease, the week of pregnancy and the development of fetus at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…The evidence for the selection and use of a chemotherapeutic regimen during pregnancy is limited due to the low incidence of this treatment. Only a few case reports have described the use of a paclitaxel and S-1 regimen during pregnancy, and the baby was reported to be within the normal limits for height, weight and neurological development, although mild intrauterine growth retardation was initially observed (7). The US Food and Drug Administration safety rating for the use of oxaliplatin and 5-FU during pregnancy is class D. Congenital fetal abnormalities have been reported in a number of pregnancies in which 5-FU was administered during the first trimester, with a reported rate of 14% to 19% (8).…”
Section: Discussionmentioning
confidence: 99%
“…First is the importance of administering chemotherapy as soon as possible after diagnosis. Second is the importance of continuing the pregnancy as long as possible to ensure the safety of the fetus 13. Ueo et al11 reported that treatment of pregnancy-associated gastric cancer depends on gestational age and the stage of the gastric cancer.…”
Section: Discussionmentioning
confidence: 99%